Mixed barium‐lead borate glasses studied by optical and vibrational spectroscopy. (21st February 2019) - Othman, Hosam A.; Herrmann, Andreas; Möncke, Doris
Abstract: Glasses of the ternary lead‐barium borate series (70− x ) B2 O3 –30 BaO– x PbO with x  = 0.05 to 30 mol% were studied for their optical properties by photoluminescence (PL) and UV‐Vis absorption spectroscopy. Variations in the s‐p transition of Pb 2+ were followed as variations of the lead content and varying optical basicities of the glass. The UV cutoff of the undoped glass sample is observed at about 340 nm and increasing PbO addition results in a red shift of the optical absorption edge to 480 nm for the glass with x  = 30 mol%. In lead barium borate glasses, the emission intensity increases up to 4 mol% PbO before decreasing at higher PbO levels. Additionally, the series was studied regarding structural variations by Raman and infrared spectroscopy. The fraction of tetrahedrally coordinated [BO4/2 ] − and of trigonal borate units with nonbridging oxygen atoms (metaborate and pyroborate) increases with PbO addition. The molar volume of the prepared glasses is found to increase with increasing lead content. The glass basicity, as determined from the composition, correlates well with the position of the lead excitation band.